CMA 103 - Medical Terminology & Body Systems 3 - Linn Benton Virtual College (2018)
This course prepares the student to list major specialties in medicine, allied health, and their qualifications as well as their contribution to the overall health care system. The student will be able to discuss acute and chronic body system diseases, processes, and failures addressed by these major specialties and branches of allied health, as well as common treatment modalities for each system and how these might change throughout the lifespan.